An update on the detection and treatment of Rickettsia felis - Hun Opfer, Ruchilia Laya (2012)
Rickettsia felis was described as a human pathogen almost two decades ago, and human infection is currently reported in 18 countries in all continents. The distribution of this species is worldwide, determined by the presence of the main arthropod vector, Ctenocephalides felis (Bouché). The list of symptoms, which includes fever, headache, myalgia, and rash, keeps increasing as new cases with unexpected symptoms are described. Moreover, the clinical presentation of R. felis infection can be easily confused with many tropical and nontropical diseases, as well as other rickettsial infections. Although specific laboratory diagnosis and treatment for this flea-borne rickettsiosis are detailed in the scientific literature, it is possible that most human cases are not being diagnosed properly. Furthermore, since the cat flea infests different common domestic animals, contact with humans may be more frequent than reported. In this review, we provide an update on methods for specific detection of human infection by R. felis described in the literature, as well as the treatment prescribed to the patients. Considering advances in molecular detection tools, as well as options for as-yet-unreported isolation of R. felis from patients in cell culture, increased diagnosis and characterization of this emerging pathogen is warranted.